What Factors Drove the Global Cropland Expansion Into Highlands? - Wanxu Chen; Yanghaoyue Yuan; Tianci Gu; Haitao Ma; Jie Zeng (Earth's Future, 2025)
Abstract The escalating demand for agricultural land, along with limited availability in lowland areas, has driven cropland expansion into highlands (CEIH), potentially resulting in land degradation, habitat degradation, and a decline in food production. However, few studies thoroughly investigated the distribution and driving factors of global CEIH, even though a considerable amount of cropland has extended to the highlands over recent decades. To investigate CEIH, we employed spatial statistics, elevation spectrum analysis, and terrain gradient methods to quantify spatio‐temporal patterns and elevation changes in global cropland distribution from 1995 to 2020. We then explored the key driving factors of CEIH at different scales using spatial regression models and multiscale geo‐weighted regression model. The results revealed that global average cropland elevation increased from 422.782 m in 1995 to 427.321 m in 2020, representing a 4.539 m net increase. CEIH was reflected on both global and continental scales in all continents except South America during the study period. Furthermore, CEIH showed an intense agglomeration pattern. Human activities and cropland reclamation rate emerged as the primary underlying driving factors of CEIH. The encroachment of development on lowland agricultural areas forced CEIH, which was the core of this phenomenon. Vertical cropland expansion was predominantly concentrated in ecologically vulnerable highlands and ecological transition zones. The driving factors of CEIH exhibited spatial and multiscale heterogeneity. These findings provided a scientific basis for formulating targeted cropland conservation policies by highlighting the differences in cropland management performance across various levels of government globally.